Improved harmonic performance of cascaded H-Bridge converters with thermal control - Monopoli, Vito Giuseppe; Marquez, Abraham; Leon, Jose I.; Ko, Youngjong; Buticchi, Giampaolo; Liserre, Marco (Institute of Electrical and Electronics Engineers, 2018)
Among multilevel converter topologies, the cascaded H-bridge converter (CHB) is one suitable solution for multiple applications such as flexible ac transmission systems and motor drives. CHB presents a natural high modularity because it is formed by the serial connection of H-bridges. This paper deals with a CHB where the cells do not have the same aging because the maintenance during the years of operation forces to replace some damaged cells of the converter with new or repaired ones. A method based on clamping one power cell can be used to reduce the power losses of that cell reducing its temperature and increasing its lifetime. However, clamping one cell of the CHB introduces high harmonic distortion around twice the carrier frequency due to the CHB unbalanced operation when a conventional phase-shifted PWM is applied. A deep harmonic distortion analysis of the CHB output voltage with thermal control based on clamping one cell is presented. Using this analysis, the harmonic distortion at twice the carrier frequency is eliminated applying a non-conventional phase-shifted PWM where the angles between the carriers of consecutive power cells are modified. Experimental results show how the thermal control applying the clamping of a power cell is achieved whilst the harmonic distortion around twice the carrier frequency is eliminated.